Stenosis of the trunk of the left coronary artery in idiopathic pulmonary hypertension. Case report - Sergei N. Ivanov; Alexander G. Edemskiy; Oksana Ya. Vasiltseva; Aleksandr M. Chernyavskiy; Maria V. Kalashnikova; Svetlana V. Seletskaya (ZAO "Consilium Medicum", 2023)
The manuscript presents a clinical case of treatment of a patient with idiopathic pulmonary hypertension and a rare complication left main coronary artery stenosis caused due to compression by the dilated pulmonary artery. This complication was clinically manifested by chest pain. The patient underwent percutaneous coronary angioplasty with stenting of the left main coronary artery and subsequent prescription of combined PAH-specific therapy. During the late follow-up examination in addition to clinical improvement and the absence of pain, 6-minute walking test distance increase, positive dynamics of echocardiography, right heart catheterization, as well as the laboratory marker of heart failure NT-proBNP were noted.